The effects of freeze drying and freeze drying additives on the prothrombin time and the international sensitivity index. - Poller, L (1999)
AIM: To determine whether freezing, freeze drying protective additives, or freeze drying of plasma samples from patients on coumarin treatment and from normal individuals affects prothrombin times or the international sensitivity index (ISI) calibration. METHODS: The effect of the addition of the protective additives singly and combined on the prothrombin time of coumarin samples and normal samples before and after freeze drying was observed using high and low ISI reference thromboplastins. ISI values were also determined. RESULTS: Freezing caused a prolongation of prothrombin time in the normal plasma samples with both reagents, which was significant with the low ISI human. Prolongation (non-significant) of the prothrombin time in coumarin plasma samples occurred with the human reagent only. Significant prolongation of normal prothrombin time by some of the protective additives before and after freeze drying was observed with both thromboplastins but to a greater extent with the human. Significant prolongation of prothrombin time in coumarin plasma samples was observed, but again was more marked with human thromboplastin. An approximate ISI was determined on the 20 coumarin samples. The only marked ISI change was with the WHO human thromboplastin after freeze drying of plasma, where a decrease from 0.95 to 0.90 was observed, corresponding to a marked prothrombin ratio increase. CONCLUSIONS: Freeze drying additives and the freeze drying procedure prolong normal and coumarin prothrombin times, with low ISI thromboplastin. Less marked prolongations occurred with a high ISI rabbit reagent, coumarin samples showing more significant prolongations. Marked ISI change in freeze dried plasma was only recorded with the low ISI ECAA human reagent. Frozen normal plasma samples cannot be used with confidence for ISI calibrations.